Avaliação de métodos na produção de biofilme em Staphylococcus spp. isolados de hemoculturas de unidade de terapia intensiva adulta - Carvalho, Fernanda Aguirre (2017)
Intensive Care Units (ICUs) are intended for the care of critically ill patients who need continuous monitoring and support of their vital functions. These are 5 to 10 times more likely to contract with Bloodstream Infections, and this risk is directly proportional to disease severity, nutritional conditions, the nature of diagnostic or therapeutic procedures, and length of stay. ICS indicates the presence of viable microorganisms in the bloodstream and is often associated with a considerable increase in morbidity and mortality rates. In addition to being one of the most significant complications in the infectious process, CSIs become of great diagnostic relevance. In blood cultures, Gram-positive cocci have emerged as the main agents recovered, especially Staphylococcus aureus, Staphylococcus coagulase negative and Enterococcus spp. Staphylococcus spp. are frequently involved in biofilm-associated infections, as this is one of the defense mechanisms of the genus, which is composed of bacteria known to be commensal to human skin and mucous membranes, which places them in a strategic place to infect any medical device that penetrates these surfaces . In biofilm, these bacteria present a sessile lifestyle, generally less susceptible to antimicrobials than their planktonic forms, providing an environment of protection against external pressures, against the action of the immune system and facilitates the interaction of cells with host organism. This work aimed to evaluate four different methods in the production of biofilm in Staphylococcus spp. isolated from blood cultures of patients hospitalized in the adult ICU of the Hospital Universitário de Santa Maria, from April 2016 to April 2017. During this period, 797 requests for blood cultures in the ICU were requested. Of these 89 positivated, being 54 of the genus Staphylococcus spp. which were selected for this study. To evaluate the biofilm production, the isolates were tested using 4 different methods: polystyrene plate adhesion (MTP), considered gold standard; borosilicate (TM) tube; Congo red agar (CRA); search for icaACD (genotypic) genes. The antimicrobial susceptibility profile was analyzed by automated methodology (Vitek Biomerieux, France). In 59.25% (32/54) of the isolates biofilms were produced by one or more of the four methodologies tested. Biofilm was detected in 57.41% (31/54) of the isolates of Staphylococcus spp. by the MTP method, 24.07% (13/54) by the CRA and 11.11% (6/54) by the TM. In the genotype only seven isolates (12.95%) expressed the icaACD genes and two isolates (3.70%) the icaAD genes. Regarding the sensitivity profile, biofilm isolates were more resistant to antimicrobials than non-producers. Through these results we can conclude that compared to the methodology considered gold standard (MTP), CRA and TM did not present reliable values to suggest its use in the evaluation of biofilm production in the routine. Regarding the genotypic test, the importance of new studies for the evaluation of mechanisms of biofilm-independent production is highlighted.